Characteristics of Gastric Mucosa-associated Lymphoid Tissue Lymphoma in Korea - Tae-Woo Kim; Joon Sung Kim (The Korean Journal of Gastroenterology)
The prevalence of gastric mucosa-associated lymphoid tissue (MALT) lymphoma in Korea has not been reported largely because, it is a relatively rare disease. Gastric MALT lymphoma is clinically important because of the high prevalence of Helicobacter pylori (H. pylori) in Korea. The endoscopic findings of gastric MALT lymphoma are diverse, and it is often challenging to differentiate from gastric adenocarcinoma. Adequate tissue acquisition and testing for H. pylori are required for diagnosis. Neck, chest, and abdominopelvic CT scans should be performed with detailed patient history taking and a physical examination for accurate disease staging. The treatment for gastric MALT lymphoma depends on the disease stage and include H. pylori eradication therapy, radiation therapy, and chemotherapy. This manuscript summarizes the etiology, clinical characteristics, diagnosis, and treatment of gastric MALT lymphoma in Korea.